The Effect of Shift Timing on Cesarean Delivery Outcomes and Operative Noise Levels - Smith, Gabrielle K.; Ulin, Mara A.; Ganjineh, Brandon M.; Urban, Amanda R.; Fuller, Robert R.; Whitham, Megan D. (American Journal of Perinatology, 2024)
Objective Intraoperative noise exposure has been associated with an increased risk of complications, communication errors, and stress among surgical team members. This study evaluates intraoperative noise levels in cesarean deliveries during different shift times, for example, night shifts, day shifts, and hand-off times between shifts.Study Design This is a secondary analysis of a prospective observational study which measured volume in decibels, percentage of time above safe levels (>60 dB), startle noise events (events with rapid increase of decibel level above baseline noise), and peak levels (>75 dB) for cesarean deliveries during a 3-month preintervention and postintervention study. This secondary analysis of noise data evaluated whether there were differences in noise for cases occurring during day shifts (6:31 a.m.–4:59 p.m.), night shifts (6:01 p.m.–5:29 a.m.), and hand-off times (5:30 a.m.–6:30 a.m. and 5:00 p.m.–6:00 p.m.). Correlates and postoperative complications during the respective shifts were additionally analyzed.Results Noise data were collected for a total of 312 cesarean deliveries; 203 occurred during the day shift, 94 during the night shift, and 15 during hand-off times. Median noise in decibels, median noise at various key intraoperative points, number of startle events, percentage of time above 60 dB, and above 75 dB had no significant differences throughout the various shift times. Significantly larger numbers of postpartum hemorrhages, unscheduled, urgent, and STAT cesarean deliveries occurred at hand-off times and on night shifts.Conclusion Noise levels during cesarean deliveries did not significantly vary when comparing night shifts, day shifts, and hand-off times, despite significantly higher numbers of urgent and STAT cases occurring overnight and during hand-off times. However, more than 60% of case time had noise levels exceeding those considered safe. This suggests that ambient background noise may be contributing more to overall noise levels rather than the specific clinical scenario at hand.Key Points
Keywords: cesarean delivery; hand-offs; maternal outcomes; neonatal outcomes; noise; shifts; sound